2017
DOI: 10.1103/physrevd.96.064046
|View full text |Cite
|
Sign up to set email alerts
|

Scalarization of neutron stars with realistic equations of state

Abstract: We consider the effect of scalarization on static and slowly rotating neutron stars for a wide variety of realistic equations of state, including pure nuclear matter, nuclear matter with hyperons, hybrid nuclear and quark matter, and pure quark matter. We analyze the onset of scalarization, presenting a universal relation for the critical coupling parameter versus compactness. We find that the onset and the magnitude of the scalarization are strongly correlated with the value of the gravitational potential (th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Damour and Esposito-Farèse [46][47][48][49] discovered the effect of spontaneous scalarization beyond a critical compactness, which, more recently, was reconsidered by the authors of Refs. [50,51]. Spontaneous scalarization as a Higgslike mechanism in which a photon gains mass is studied in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Damour and Esposito-Farèse [46][47][48][49] discovered the effect of spontaneous scalarization beyond a critical compactness, which, more recently, was reconsidered by the authors of Refs. [50,51]. Spontaneous scalarization as a Higgslike mechanism in which a photon gains mass is studied in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated that spontaneous scalarization features as prominently in rotating NS models, either in the slow-rotation limit [32][33][34][35][36][37], for fast rotation [38,39], or with differential rotation [40]. Spontaneous scalarization has also been found a robust phenomenon under variations of the Equation of state (EOS) [21,36,[41][42][43]. While quantitative differences occur, the phenomenon as such appears to be ubiquitous and also preserve the approximate EOS universality of the relation between the moment of inertia I and the quadrupole moment Q known from GR [33,39] and the inertia vs. compactness universality [36].…”
Section: Introductionmentioning
confidence: 99%
“…Spontaneous scalarization has also been found a robust phenomenon under variations of the Equation of state (EOS) [21,36,[41][42][43]. While quantitative differences occur, the phenomenon as such appears to be ubiquitous and also preserve the approximate EOS universality of the relation between the moment of inertia I and the quadrupole moment Q known from GR [33,39] and the inertia vs. compactness universality [36].…”
Section: Introductionmentioning
confidence: 99%
“…For the SNMC, (dF/dΦ)| Φ0 ∝ Φ 0 , and so the observed agreement [7] between solar system observations and GR's predictions implies that Φ 0 must be close to zero-but does not limit the viable range of ξ. Interestingly, however, even if Φ 0 = 0, STTs may still differ considerably from GR in their predictions for neutron stars (NS), due to a nonperturbative, strong-field effect known as spontaneous scalarization [8]. This effect, which has long been known to happen for sufficiently negative values of the nonminimal coupling ξ, is characterized by the formation of a scalar cloud that modifies the star's equilibrium * rfpmendes@id.uff.br † tulioottoni@id.uff.br and perturbative properties [9][10][11][12][13], and has dramatic implications, most notably for pulsar-timing observables [14][15][16]. Indeed, the inconsistency between pulsar-timing data and certain aspects of NS phenomenology in STTs, such as the existence of scalar dipole radiation, of scalarfield induced variations in the NS moment of inertia, and so on, can be used to rule out almost the entire range ξ −2.2 of field couplings allowing for spontaneous scalarization (in the case where V (Φ) = 0, which we will refer to as "massless" for simplicity).…”
Section: Introductionmentioning
confidence: 99%